2008
DOI: 10.3758/pp.70.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Auditory event perception: The source-perception loop for posture in human gait

Abstract: There is a small but growing literature on the perception of natural acoustic events, but few attempts have been made to investigate complex sounds not systematically controlled within a laboratory setting. The present study investigates listeners' ability to make judgments about the posture (upright-stooped) of the walker who generated acoustic stimuli contrasted on each trial. We use a comprehensive three-stage approach to event perception, in which we develop a solid understanding of the source event and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 65 publications
(46 reference statements)
1
33
0
Order By: Relevance
“…Such information can be extracted by recordings of real steps occurring in those scenarios. Moreover, by leveraging the results reported by Pastore et al [25], it might be possible even to simulate two postures of the walker, i.e. upright and stooped.…”
Section: General Discussion and Conclusionmentioning
confidence: 95%
See 1 more Smart Citation
“…Such information can be extracted by recordings of real steps occurring in those scenarios. Moreover, by leveraging the results reported by Pastore et al [25], it might be possible even to simulate two postures of the walker, i.e. upright and stooped.…”
Section: General Discussion and Conclusionmentioning
confidence: 95%
“…In a different vein, Pastore et al showed that listeners are capable of identifying the posture of the walker who generated the acoustic stimuli [25], while Mäkelä et al showed that footstep sounds can convey information about the identity of a person [26].…”
Section: The Ground Truth Problemmentioning
confidence: 99%
“…The processes involved in the perception of the sound source have been described in terms of a loop (Pastore, Flint, Gaston, & Solomon, 2008): the mechanics of the sound source structures the acoustical signal (e.g., Fletcher & Rossing, 1991) and the sound properties are used to perceive the mechanical properties of the sound source (e.g., Carello, Wagman, & Turvey, 2003;McAdams, 1993). The perceptual process requires at least two decisions: first about which acoustical properties are to be taken into account (e.g., sound frequency), and second about how acoustical information should be weighted perceptually (e.g., the log perceived height of a struck plate approximately doubles with an eight-fold increase in log sound frequency, see Kunkler-Peck and Turvey, 2000, for details).…”
mentioning
confidence: 99%
“…with particular regard to those that can be seen, heard, or felt by the user during locomotion. For example, previous research has demonstrated that it is possible to recognize the walker's gender (Li et al 1991), identity (Mäkelä et al 2003), emotions (Giordano and Bresin 2006), and body posture (Pastore et al 2008) based on auditory information alone contained in footstep sounds, suggesting therefore that an appropriate auditory rendering of the user's anthropomorphic features can play an important role in the body awareness during the simulated locomotion. In addition, the present study suggests the importance of simulating the sensation of wearing specific shoes and clothes.…”
Section: Discussionmentioning
confidence: 96%
“…The objectives related to the active dimension, on the one hand, were supported by results showing that footstep sounds convey information about the gender (Li et al 1991), the footwear sole hardness (Giordano and Bresin 2006), the identity of a person (Mäkelä et al 2003), and even his/her body posture (e.g., upright, stooped) (Pastore et al 2008). On the other hand, they were supported by results indicating that affordances of an environment are perceived in body-scaled terms (Warren 1984;Mark 1987;Warren and Whang 1987;Oudejans et al 1996).…”
Section: Designing the User's Experiencementioning
confidence: 96%